2017
DOI: 10.1002/adma.201606842
|View full text |Cite
|
Sign up to set email alerts
|

Photonic Devices Out of Equilibrium: Transient Memory, Signal Propagation, and Sensing

Abstract: Soft photonic materials are important for sensors, displays, or energy management and have become switchable under static equilibrium conditions by integration of responsive polymer features. The next step is to equip such materials with the ability for autonomously dynamic and self-regulating behavior, which would advance their functionality and application possibilities to new levels. Here, this study shows the system integration of a nonlinear, biocatalytic pH-feedback system with a pH-responsive block copo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 45 publications
0
64
0
Order By: Relevance
“…The slow, enzymatic, feedback‐driven pH change creates a transient gelation process that can be programmed in time. Later, they further extended this concept to a photonic gel, which demonstrates autonomous transient memories, remotely controlled signal propagation, and sensing . With the aid of such a powerful tool, time‐lapse polymerization, self‐regulated microgels or supramolecular gels, and self‐adaptive nanoreactors have been successfully demonstrated.…”
Section: Figurementioning
confidence: 99%
“…The slow, enzymatic, feedback‐driven pH change creates a transient gelation process that can be programmed in time. Later, they further extended this concept to a photonic gel, which demonstrates autonomous transient memories, remotely controlled signal propagation, and sensing . With the aid of such a powerful tool, time‐lapse polymerization, self‐regulated microgels or supramolecular gels, and self‐adaptive nanoreactors have been successfully demonstrated.…”
Section: Figurementioning
confidence: 99%
“…Moreover, it was also demonstrated that their temporary hydrogels could release hydrophilic dye after a preprogrammed time (Figure d). Because of the generality of the principle, several other assemblies have been formed via this principle including DNA i‐motifs and photonic devices …”
Section: Supramolecular Materials With a Tunable Lifetimementioning
confidence: 99%
“…Because of the generality of the principle, several other assemblies have been formed via this principle including DNA i-motifs [61] and photonic devices. [62] To demonstrate the use of dissipative materials as delivery vehicles, we recently described the release of hydrophobic dyes from a dissipative supramolecular material. We used Fmocprotected glutamic acid (Fmoc-E, Figure 8a) as a precursor in the carbodiimide-fueled chemical reaction network described in Figure 3a.…”
Section: Temporary Materials As Delivery Devicesmentioning
confidence: 99%
“…[13] Moreover, peptides can be chemically modified by conjugation with aromatic groups or aliphatic tails which can further enhance their propensity for self-assembly. In this regard, fluorenyl protected peptides, [14][15][16][17][18] lipopetides [19,20] and peptide amphiphiles [21][22][23][24] have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%